Pragmatic Knowledge Typology in Second Language Mastering (Eurasian Journal of Philology Science and Education, 2015)
Research of pragmatic orientation issues in terms of mastering a second / foreign language are being expanded and specified through the use of the current research results in the field of pragmatics, cross-cultural communication and linguodidactics. This article investigates the pragmatic paradigm of a second language acquisition process as a body of knowledgethat ensures mastering of a second language when solving the issues of a secondary linguistic identity socialization in a foreign language environment (communicative competence formation) , as well as the acquisition and application of social and national and cultural knowledge. Typology of pragmatic knowledge is considered in the context of pragmatics of communication, pragmatics of text, and pragmatics of speech. A classification of pragmatic knowledge is specified as well: declarative and procedural, extralinguistic and intralinguistic . This issue is of great importance from the perspective of learning Russian as a second language in terms of thetitular nation’s language dominance in the southern regions of the country.
Keywords: second language; pragmatic paradigm; typology of knowledge